The democracy advantage how democracies promote prosperity and peace - Halperin, Morton H. (New York Routledge, 2005)
Reviewing 40 years of hard, empirical data, from China and India to Chile and Iraq, the authors show that poor democracies beat poor autocracies in every economic measure. In addition, the authors offer dramatic evidence that democracies are less likely to fight each other and that terrorists more often find safe haven in authoritarian countries such as Egypt, Saudi Arabia, and Pakistan.
Includes bibliographical references (p. 271-282) and index.
Keywords: Democracy